Algoritma Genetika untuk Pemecahan Masalah Rute Kendaraan dengan Ukuran dan Campuran Armada, Trip Majemuk, Pengiriman Terbagi, Produk Majemuk, dan Kendaraan dengan Kompartemen Majemuk - Suprayogi Suprayogi; Daniel Bunga Paillin (Jurnal Teknik Industri, 2017)
This paper discusses a variant of the basic vehicle routing problem (VRP) by including the following characteristics: fleet size and mix, multiple trips, split delivery, and multiple compartments. One of real cases of this problem is related to determining tanker’s routes in delivering fuel products from a supply port to a number of destination ports. Each tanker has several compartments where each compartment is dedicated to a certain fuel product. In this paper, a solution approach based on genetic algorithm (GA) is proposed and tested using nine hypothetical instances. Experiment results show that the proposed GA gives consistent results measured by coefficient variations